Two new species of Papuagrion Ris, 1913 (Odonata: Coenagrionidae) from New Guinea with a survey of distribution records for the genus - Orr, A.g.; Kalkman, V.j. (Zootaxa, 2016)
Two new species of Papuagrion Ris, 1913 are described from Papua Province, Indonesia. These are P. marirobi sp .nov. from Japen Island and P. stellimontanum sp .nov., from the Star Mountains. The new species are, respectively, most closely allied to P. degeneratum Lieftinck and P. digitiferum Lieftinck. They bring the number of Papuagrion species to 28. New locality records of several other species are noted.